P454 Emergency Department (ED)-based HIV Pre-Exposure Prophylaxis (PrEP) referral program – using EDs as a portal for PrEP services. (14th July 2019) - Zhao, Zezhou; Jones, Joyce; Sanders, Renata; Gladfelter, Gaby; Mcdonald, Steven; Reed, Christopher; Castellanos, Jojo; Fulton, Glenn; Motley, Kaitlynn; Campbell, Eric; Myer, Deanna; Jones, Tiana; et al.
Abstract : Background: U.S. Emergency Departments (EDs) serve many patients at high risk for HIV and could serve as a portal of entry for pre-exposure prophylaxis (PrEP). We conducted a pilot study to determine feasibility and acceptability of PrEP referral from the ED. Methods: From late December 2018 to March 2019, a pilot PrEP referral program was integrated into an established HIV/HCV screening program in an urban U.S. ED with HIV seroprevalence of 6%. Patients were deemed PrEP referral eligible if they had recent STI-related visit (<2 months) and tested HIV negative, or a negative HIV test during the current ED visit. The PrEP referral program was implemented by HIV/HCV program staff and trained volunteers. Patients were approached by convenience sampling based on staff availability. HIV risk and interest in PrEP referral was assessed through an electronic survey based on CDC PrEP guidelines. Patients expressing interest in PrEP were referred to PrEP peer navigators from the adult infectious disease specialty clinic and pediatric clinic. Referrals, scheduled and completed appointments, and PrEP initiation were collected. Results: In this ongoing program, 290 ED patients were screened, 162 approached and 89 (55%) took the survey. 68 (42%) were categorized as high-risk and eligible for PrEP referral. Of these 68 patients, 36 (53%) accepted PrEP referral, 15 (22%) were successfully contacted by phone with additional 21 (31%) pending for follow-up calls, six (9%) were scheduled for appointments, and two (3%) completed an appointment. Conclusion: Our preliminary findings demonstrate a high interest for PrEP referral and comparable PrEP care cascade outcomes in high-risk ED patients indicating that implementation of an ED-based PrEP referral program is feasible and acceptable and could serve as an important portal for PrEP care. Barriers along the PrEP care continuum to better engage and retain patients should be addressed as a future direction. Disclosure: No significant relationships.